2016
DOI: 10.1002/jbm.a.35739
|View full text |Cite
|
Sign up to set email alerts
|

Novel hydrophilic nanostructured microtexture on direct metal laser sintered Ti-6Al-4V surfaces enhances osteoblast responsein vitroand osseointegration in a rabbit model

Abstract: The purpose of this study was to compare the biological effects in vivo of hierarchical surface roughness on laser sintered titanium-aluminum-vanadium (Ti-6Al-4V) implants to those of conventionally machined implants on osteoblast response in vitro and osseointegration. Laser sintered disks were fabricated to have micro-/nano-roughness and wettability. Control disks were computer numerical control (CNC) milled and then polished to be smooth (CNC-M). Laser sintered disks were polished smooth (LST-M), grit blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 56 publications
2
42
1
5
Order By: Relevance
“…Recent studies comparing porous constructs and solid implants, both with clinically relevant surface treatments showed comparable mechanical force to failure even though porous implants had bone ingrowth whereas solid implants had bone on‐growth (Cheng, Humayun, Boyan, & Schwartz, ; Cheng, Humayun, & Cohen, ; Hyzy et al, ). These earlier studies did not examine the effects of differing porous architecture while maintaining pore size and porosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies comparing porous constructs and solid implants, both with clinically relevant surface treatments showed comparable mechanical force to failure even though porous implants had bone ingrowth whereas solid implants had bone on‐growth (Cheng, Humayun, Boyan, & Schwartz, ; Cheng, Humayun, & Cohen, ; Hyzy et al, ). These earlier studies did not examine the effects of differing porous architecture while maintaining pore size and porosity.…”
Section: Discussionmentioning
confidence: 99%
“…However, for implants that depend on bone ingrowth for stability, there is still debate on the optimal architecture and pore properties for enhanced osseointegration. Porous implants support increased bone ingrowth, although a study comparing AM fabricated porous implants with solid implants in rabbit tibial bone defects and in a rat calvarial on‐lay model for vertical bone ingrowth, showed that the porous implants were comparable to their solid counterparts concerning pull out force to failure (Cheng, Cohen, et al, ; Hyzy et al, ). The specific properties of the pores can also affect outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the range of periodicity of the line-like structures that were chosen for this study (3- surfaces with line-like structures with spatial periods smaller than 3 μm as well as larger than 20 μm. Previous studies demonstrated that roughing the surface of titanium seems to have the potential of promoting osseointegration (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has shown that laser sintered Ti-6Al-4V solid implants placed in rabbit tibia cortical bone perform better than traditional implants manufactured with computer numerical control (CNC) [17]. We have also shown in previous studies that use of an osteoinductive agent (DBX, Musculoskeletal Transplant Foundation, Edison, New Jersey, USA) on rat calvaria did not alter the mechanical pull-out strength or new bone volume analyzed by microCT of porous laser sintered implants at 10 weeks postoperatively [13].…”
Section: Discussionmentioning
confidence: 99%
“…These results combined with in vivo studies demonstrating the ability of laser sintered implants to perform as well as implants manufactured with conventional techniques in animal models [17, 18], suggest that laser sintered implants with trabecular bone-inspired porosity may be superior to solid implants and enhance osseointegration in challenging clinical cases. While these results are promising, osseointegration of implants with trabecular bone-inspired porosity has not yet been analyzed in a clinically relevant orthopaedic or dental animal model.…”
Section: Introductionmentioning
confidence: 99%